A robust method for assessing chemically induced mutagenic effects in the oral cavity of transgenic Big Blue® rats. (13th May 2015) - Young, Robert R.; Thompson, Chad M.; Dinesdurage, Harshini R.; Elbekai, Reem H.; Suh, Mina; Rohr, Annette C.; Proctor, Deborah M.
<x xml:space="preserve">Abstract</x> The Big Blue® (BB) in vivo mutation assay uses transgenic rodents to measure treatment‐induced mutations in virtually any tissue. The BB assay can be conducted in rats or mice and is ideal for investigating tissue‐specific mutagenic mode of action of tumor induction. Some tissues such as oral mucosa have not been thoroughly studied. Due to the small quantity and cartilaginous nature of oral cavity tissues, development of special prosection and DNA isolation methods was required to permit robust analysis of mutations in these tissues. Improved surgical methods permitted collection of adequate and reproducible quantities of tissue (∼45 mg gingiva/buccal and ∼30 mg gingiva/palate). Optimized DNA isolation methods included use of liquid nitrogen pulverization, homogenization, nuclei pelleting, digestion, and phenol/chloroform extraction, to yield sufficient quantities of DNA from these tissues. In preliminary optimization work, mutant frequency (MF) in tongue and gingiva was increased in rats exposed to the promutagen, benzo[a]pyrene, and the direct mutagen, N‐ethyl‐N‐nitrosourea. The oral cavity carcinogen, 4‐nitroquinoline‐1‐oxide (4‐NQO; 10 ppm in drinking water; 28 days), was qualified as a positive control for mutagenesis in oral tissues since it caused significant increases in cII MFs in gingiva/palate (50.2‐fold) and gingiva/buccal tissues (21.3‐fold), but not in liver or bone marrow (0.9‐ and 1.4‐fold, respectively). These results are consistent with the observation that 4‐NQO primarily induces tumors in oral cavity. Results also demonstrate the utility of the BB rat mutation assay and optimized methods for investigation of oral cavity mutagenicity, and by extension, analysis of other small and cartilaginous tissues. Environ. Mol. Mutagen. 56:629–636, 2015. © 2015 Wiley Periodicals, Inc.